2021
DOI: 10.1038/s41598-021-86313-z
|View full text |Cite
|
Sign up to set email alerts
|

Injury alters motivational trade-offs in calves during the healing period

Abstract: Injury can produce long-lasting motivational changes that may alter decisions made under risk. Our objective was to determine whether a routine painful husbandry procedure, hot-iron disbudding, affects how calves trade off risk avoidance against a competing motivation (i.e., feeding), and whether this response depends on time since injury. We used a startle test to evaluate this trade-off in calves disbudded 0 or 21 days previously and non-injured control calves. For 3 days, calves were individually habituated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Alternatively, Theurer et al reported that calves treated with NSAIDs spent less time in the hay feeder 57 and Adcock and Tucker reported that disbudded calves spent more time suckling milk due to its soothing effect or a need to meet increased energy requirements 31 . Thus, our disbudded pair-housed calves might have placed a higher value on eating forage due to a need to meet increased energy requirements and/or a soothing effect through oral manipulation, which would suggest the opposite, i.e., that pair-housed calves were affected by disbudding more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Theurer et al reported that calves treated with NSAIDs spent less time in the hay feeder 57 and Adcock and Tucker reported that disbudded calves spent more time suckling milk due to its soothing effect or a need to meet increased energy requirements 31 . Thus, our disbudded pair-housed calves might have placed a higher value on eating forage due to a need to meet increased energy requirements and/or a soothing effect through oral manipulation, which would suggest the opposite, i.e., that pair-housed calves were affected by disbudding more.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we predicted that pair-housed calves would have a smaller decrease in those behaviors which indicate improved welfare after disbudding (i.e., in feeding, ruminating, resting, exploration, and play), but smaller increase in pain-related behaviors (i.e., head shaking, head rubbing, foot stamping, and self-grooming) than individually housed calves. It seems that feeding does not change after disbudding 27 30 , but Adcock and Tucker reported that disbudded calves spent more time suckling milk 31 , and cattle have been reported to decrease feeding after other stressful events, e.g., transportation 32 , 33 . The findings on ruminating and lying are also inconclusive as they were reported either to decrease 6 , 27 , 29 or did not change after disbudding 30 , 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Calves have been reported to be more pessimistic after disbudding and to display signs that may be interpreted as anhedonia, either consuming less of a highly desirable sweet solution (Lecorps et al, 2020) or perceiving the value of a reward that they were conditioned to expect as lower compared with before the procedure (Lecorps et al, 2019). Alternatively, using risk aversion methods, Adcock and Tucker (2021) reported disbudded calves to accept more risk compared with control calves to suckle (for up to 3 wk after disbudding) possibly as a strategy to mitigate pain, suggesting that disbudding influences motivational states for weeks after the procedure. These changes in the emotional state of calves after disbudding were previously reported to continue anywhere from 5 (Lecorps et al, 2020) to 20 d after the procedure.…”
Section: Other Indicators Of Affective Statementioning
confidence: 99%
“…Calves increase use of a shelter for at least 3 days after disbudding, which may reflect reduced sociability (Gingerich et al, 2020). Three weeks after disbudding, calves were more likely to prioritize suckling over risk avoidance compared to non-disbudded controls (Adcock and Tucker, 2021). These motivational changes likely arise from the pain and inflammation of still healing wounds.…”
Section: Disbuddingmentioning
confidence: 99%